2015
DOI: 10.1128/iai.00611-15
|View full text |Cite
|
Sign up to set email alerts
|

Streptolysin S Promotes Programmed Cell Death and Enhances Inflammatory Signaling in Epithelial Keratinocytes during Group A Streptococcus Infection

Abstract: Streptococcus pyogenes, or group A Streptococcus (GAS), is a pathogen that causes a multitude of human diseases from pharyngitis to severe infections such as toxic shock syndrome and necrotizing fasciitis. One of the primary virulence factors produced by GAS is the peptide toxin streptolysin S (SLS). In addition to its well-recognized role as a cytolysin, recent evidence has indicated that SLS may influence host cell signaling pathways at sublytic concentrations during infection. We employed an antibody arrayb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 57 publications
(145 reference statements)
3
55
0
1
Order By: Relevance
“…The results in Figures 2 and 3 indicate that both SLS-dependent inflammatory signaling responses do not require direct contact between the bacteria and host cells. As previous experiments have already demonstrated SLS-dependent p38 and NFκB activation in direct infection models 21 , similar levels of p38 or NFκB activation among the three GAS strains in the permeable membrane insert-based system would have indicated that the response required direct contact between the bacteria and host cells. Figure 4 demonstrates that this infection system may be applied to assess toxin-dependent changes in host cytotoxicity via ethidium homodimer and LDH release assays.…”
Section: Representative Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…The results in Figures 2 and 3 indicate that both SLS-dependent inflammatory signaling responses do not require direct contact between the bacteria and host cells. As previous experiments have already demonstrated SLS-dependent p38 and NFκB activation in direct infection models 21 , similar levels of p38 or NFκB activation among the three GAS strains in the permeable membrane insert-based system would have indicated that the response required direct contact between the bacteria and host cells. Figure 4 demonstrates that this infection system may be applied to assess toxin-dependent changes in host cytotoxicity via ethidium homodimer and LDH release assays.…”
Section: Representative Resultsmentioning
confidence: 97%
“…Though very consistent host responses have been observed when comparing the results of the permeable membrane insert-based infection studies with traditional direct infection studies, some notable differences in the kinetics of these host responses have been observed 21 . For example, changes in host signaling and membrane-based cytotoxicity take 30-50% longer to occur in the permeable membrane insert-based infection model than corresponding direct infection models.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations